2017
DOI: 10.1002/jssc.201700139
|View full text |Cite
|
Sign up to set email alerts
|

Purification of lignans from Fructus Arctii using off‐line two‐dimensional supercritical fluid chromatography/reversed‐phase liquid chromatography

Abstract: As a common traditional Chinese medicine, Fructus Arctii has important clinical medical values. Its main components are lignans, which are difficult to separate and analyze because of the complex composition, similar chemical structures, and close properties. In this study, an off-line two-dimensional supercritical fluid chromatography/reversed-phase liquid chromatography method, as well as an effective sample pretreatment method based on hydrophilic interaction chromatography material, was developed to enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The peak capacity for this off‐line strategy was more than double the value achieved with an online SFC × RPLC approach (7560 vs. 3000), albeit at the expense of an approximately 20‐fold increase in analysis time [53]. Similar approaches have been adapted for the analysis of amide alkaloids from Piper longum L [54], the purification of lignan compounds from Fructus Arctii [55], and the characterization of gangliosides in swine brain extract [56]. In this latter study, 153 unique gangliosides were separated, with 20 detected for the first time based on the high selectivity of this approach.…”
Section: Sfc As the First Dimension Separationmentioning
confidence: 99%
“…The peak capacity for this off‐line strategy was more than double the value achieved with an online SFC × RPLC approach (7560 vs. 3000), albeit at the expense of an approximately 20‐fold increase in analysis time [53]. Similar approaches have been adapted for the analysis of amide alkaloids from Piper longum L [54], the purification of lignan compounds from Fructus Arctii [55], and the characterization of gangliosides in swine brain extract [56]. In this latter study, 153 unique gangliosides were separated, with 20 detected for the first time based on the high selectivity of this approach.…”
Section: Sfc As the First Dimension Separationmentioning
confidence: 99%
“…The application of LC×LC prior to MS has become an important option in the analysis and purification of chemical composition in complex TCMs [19][20][21][22][23][24][25]. A number of LC×LC methods including the combination of RPLC and RPLC [22,23,25], hydrophilic interaction liquid chromatography (HILIC) and RPLC [14,24], SFC and RPLC [21,24], and IEC and RPLC [26] et al have been developed, which effectively improve the separation selectivity of different components in TCMs by combining orthogonal separation system. Regarding the extreme complexity and wide polarity of compounds in QFPD, a single LC×LC system cannot meet the requirement of selectivity and resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, thanks to the decompression of subcritical CO2 under atmospheric conditions, off-line SFC x LC coupling are much more convenient than off-line LC x LC hyphenations, when evaporation of the 1 D fractions is required. Although a specific fraction collector is needed, the fractions can be quickly evaporated and with negligible energy costs compared to LC x LC coupling [35,36]. Thirdly, recent works showed that, under optimal conditions, the sensitivity in electrospray mass spectrometry (ESI-MS) was significantly enhanced when using SFC rather than RPLC prior detection .…”
Section: Additional Advantages Of Introducing Sfc In One Of the Dimen...mentioning
confidence: 99%